Pendekatan Efek Jera dalam Budaya Kasih Sayang untuk Meningkatkan Kedisiplinan Siswa di Sekolah Kebangsaan Bandar Puteri Jaya, Kedah, Malaysia - Tambunan, May Dea Citra; Siregar, Alfin; Yaakob, Nurol Huda Binti (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
This study aims to explore the implementation of compassion-based corrective discipline as an educational strategy to address student disciplinary issues at Sekolah Kebangsaan Bandar Puteri Jaya, Sungai Petani, Kedah, Malaysia. This qualitative research employed a phenomenological approach, with participants comprising guidance and counseling (BK) teachers and students with disciplinary records. Purposive sampling was used to select participants based on specific criteria. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data condensation, data display, and conclusion-drawing techniques. Data validity was ensured through triangulation of sources, methods, and time. The findings reveal that the corrective measures applied were not conventional punishments, but rather educational projects such as flower planting, fish farming, and art activities. These projects were tailored to students’ interests and character traits, effectively fostering a sense of responsibility, patience, self-regulation, and gradually, sustainably improving discipline. The compassion-based corrective approach has proven to be effective in shaping student character through a humanistic and reflective process, rather than through fear-based or punitive methods.